"Realizacja Dharmy Buddhy w nurcie budownictwa socjalistycznego społeczeństwa": O początkach drogi do legalizacji pierwszej wspólnoty buddyjskiej w PRL - Skrzyński, Przemysław (Studia religiologica, 2021)
The pioneering community of Polish Buddhists called "Zen Circle", operating in the 1970s, raised well-founded concerns of national public and administrative order bodies. This group, derived mainly from artistic and hippie environments, should be considered one of the most original and radical manifestations of an alternative and contesting culture to the reality of the People’s Republic of Poland. At the same time, the effectiveness of the activities undertaken by the community in the administrative field, led to a precedent situation in which its religious and non-religious activities were legalized. In this article, I reconstruct the administrative efforts made in the first period of community activity (1975-1978), but above all, I analyze the attitudes and motivations of the parties involved in the above-mentioned process: community members, decision-making officials and services responsible for the internal security of the country. Based both on the group's internal materials and interviews with members, as well as on documents prepared by state bodies, I analyze the process of shaping the identity of the first Polish Buddhists.